The Religious Practices of Deaf Muslims in Malaysia: A Case Study at the Special Education School - Mohad, Abd Hakim; Mokhtar, Ros Aiza Mohd; Omar, Nizaita (INSANCITA, 2018)
ABSTRACT: The religious practice in everyday life is part of the manifestation of religion and belief of every human being. Within the Islamic context, for example, religious practices must be one that stems from the Islamic religious laws. All Muslims, including the deaf, need to perform their religious obligations within their abilities. However, not much attention is given to people with disability, such as the deaf, with regards to observing their religious practices and in understanding the related problems that they face. This article serves to explain religious practices of the deaf Muslims through a research conducted at a Special Education School (for the Deaf) in Kota Kinabalu, Sabah and the Activity Centre, Society for the Welfare of the Deaf in Terengganu, Malaysia. This study employs the survey method, which uses the questionnaire as an instrument for data collection. Among the aspects of religious practices observed are acts of worship like prayer and fasting, as well as general practices like eating habits, and ways of dressing. The study showed that the hearing impaired also perform religious practices in their daily life, although a majority of them are unable to perform them completely. KEY WORD: Religious Practices; Deaf; Muslim in Malaysia; Ability; Special Education School.Â ABSTRAKSI: âAmalan Keagamaan Orang Islam Pekak di Malaysia: Kajian Kes di Sekolah Pendidikan Khasâ. Amalan beragama dalam kehidupan seharian merupakan sebahagian dari manifestasi agama dan kepercayaan yang pegang oleh setiap insan. Dalam konteks Islam, misalnya, amalan beragama itu mestilah sesuatu yangÂ  bersumberkan dari syariat Islam. Semua umat Islam, termasuklah golongan pekak, perlu melaksanakannya mengikut kadar kemampuan masing-masing. Namun, tidak ramai yang mengambil perhatian terhadap golongan OKU (Orang Kurang Upaya), seperti golongan pekak, untuk melihat amalan beragama yang mereka lakukan dan memahami masalah yang mereka hadapi. Makalah ini menjelaskan amalan beragama golongan pekak Muslim menerusi satu kajian yang dilakukan di Sekolah Pendidikan Khas (Pekak) di Kota Kinabalu, Sabah dan Pusat Aktiviti, Persatuan Kebajikan Pekak di Terengganu, Malaysia. Kajian menggunakan kaedah survey, dengan instrumen soal selidik bagi pengumpulan data. Antara aspek amalan beragama yang dilihat ialah amal ibadah khusus seperti solat dan puasa, juga amalan umum seperti kebiasaan pemakanan, dan cara berpakaian. Hasil kajian mendapati bahawa golongan pekak turut melaksanakan amalan beragama dalam kehidupan mereka, walaupun sebahagian besar daripada mereka tidak dapat melaksanakan dengan sempurna. KATA KUNCI: Amalan Beragama; Pekak; Muslim di Malaysia; Keupayaan; Sekolah Pendidikan Khas.Â Â Â Â About the Authors: Dr. Abd Hakim Mohad is a Senior Lecturer at the Sociology and Social Anthropology Center of Core Studies, Faculty of Leadership and Management USIM (Islamic Science University of Malaysia), Bandar Baru Nilai, 71800 Nilai, Negeri Sembilan, Malaysia. Dr. Ros Aiza Mohd Mokhtar is a Senior Lecturer at the Islamic Thoughts & Civilizations Center of Core Studies, Faculty of Leadership and Management USIM, Bandar Baru Nilai, 71800 Nilai, Negeri Sembilan, Malaysia. Assoc. Prof. Dr. Nizaita Omar is a Lecturer at the Islamic Law Department, Fakulti Pengajian Umum dan Pendidikan Lanjutan UnisZA (University of Sultan Zainal Abidin), Kampus Gong Badak, 21300 Kuala Terengganu, Terengganu, Malaysia. E-mails address: abdhakim@usim.edu.my, rosaiza@usim.edu.my, and nizaitaomar@unisza.edu.mySuggested Citation: Mohad, Abd Hakim, Ros Aiza Mohd Mokhtar & Nizaita Omar. (2018). âThe Religious Practices of Deaf Muslims in Malaysia: A Case Study at the Special Education Schoolâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Volume 3(1), February, pp.51-64. Bandung, Indonesia and BS Begawan, Brunei Darussalam: Minda Masagi Press owned by ASPENSI and BRIMAN Institute, ISSN 2443-1776. Article Timeline: Accepted (November 10, 2017); Revised (January 15, 2018); and Published (February 28, 2018).